Perkembangan Iman Remaja Sebagai Landasan Moderasi Beragama: Perspektif James Fowler dan Konsep Fitrah Islam - Aufa Fatchia Rahma; Muqowim Muqowim (STAI Asy-Syukriyyah, 2026)
The development of adolescent religiosity in the digital era faces various challenges that can influence the formation of religious moderation. This article aims to analyze the synthesis of James W. Fowler's theory of faith development and the concept of fitrah in Islam as a conceptual framework for understanding the dynamics of adolescent faith development and building resilience to faith-based moderation. This study uses a qualitative approach with a library research method. Data were obtained from books, scientific journal articles, and academic documents discussing Fowler's theory of faith development, the concept of fitrah in Islam, adolescent developmental psychology, tolerance, and religious moderation. Data analysis was conducted using content analysis techniques with the stages of identification, categorization, interpretation, and synthesis of concepts to find common ground between the two perspectives. The results of the study indicate that Fowler's stages of faith development, particularly the transition from the synthetic-conventional to the individuative-reflective stage, are relevant to the concept of fitrah, which views humans as having a basic potential for faith that develops through education and life experiences. The integration of these two perspectives results in the understanding that a mature, reflective faith rooted in fitrah is an important foundation for the formation of a tolerant, inclusive, and moderate attitude. This finding confirms that strengthening adolescent faith through an integrated psychological and spiritual approach can be an effective strategy in supporting religious moderation in a pluralistic society.